2019
DOI: 10.1002/nbm.4128
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive quantitative magnetization transfer MRI reveals tubulointerstitial fibrosis in murine kidney

Abstract: Excessive tissue scarring, or fibrosis, is a critical contributor to end stage renal disease, but current clinical tests are not sufficient for assessing renal fibrosis. Quantitative magnetization transfer (qMT) MRI provides indirect information about the macromolecular composition of tissues. We evaluated measurements of the pool size ratio (PSR, the ratio of immobilized macromolecular to free water protons) obtained by qMT as a biomarker of tubulointerstitial fibrosis in a well‐established murine model with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 40 publications
7
56
0
Order By: Relevance
“…Paraffin tissue sections were stained with picrosirius red using standard procedure for histologic confirmation …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paraffin tissue sections were stained with picrosirius red using standard procedure for histologic confirmation …”
Section: Methodsmentioning
confidence: 99%
“…The histologic fibrosis index was evaluated using the same procedure as in our previous work Positive picrosirius red=Positive AreaTotal Area×100%…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al showed the utility of qMT in detecting renal fibrosis in mouse models of diabetic nephropathy 18 and progressive fibrosis 19 using 7.0T MRI. Because only mild or localized fibrosis developed in these models, qMT‐derived pool size ratio (PSR, the ratio between the bound and free pool magnetization) correlated with renal fibrosis by histology only in the renal cortex (CO) 18 or outer strip of outer medulla (OSOM) 19 . The ability of qMT to measure fibrosis in other structurally and functionally distinctive kidney regions, including inner strip of outer medulla, inner medulla (IM), and papilla (P), remains to be tested.…”
mentioning
confidence: 99%
“…MT can detect large immobile macromolecules distributed within tissues and evaluate pathophysiological events (e.g., fibrosis, apoptosis) accompanied by changes in macromolecular components. We and others have recently shown that renal fibrosis can be assessed using specific parameter pool-size ratio from the quantitative MT approach based on mathematical modeling or MT ratio from simpler two-point metrics [132,[134][135][136]. Importantly, changes in physiological conditions and hemodynamics can affect measurements on DWI and BOLD imaging, even in the absence of fibrosis.…”
Section: Magnetization Transfer (Mt)mentioning
confidence: 99%